Pengaruh Model Pembelajaran Think Talk Write (TTW) terhadap Keterampilan Menulis Permulaan Siswa - Bilqisti Ramadhani; Raisa Maharani (BHASWARA: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
This research was motivated by problems in the early writing skills of second-grade students at SDN 03 Salimpaung. Students still had difficulties writing letters and words correctly, showed inconsistent use of spelling, and had low ability to arrange words into simple sentences. This condition was also influenced by the use of less varied teaching methods that did not actively involve students in the processes of thinking, speaking, and writing. Therefore, this study aimed to determine the effect of the Think Talk Write (TTW) learning model on the early writing skills of second-grade students at SDN 03 Salimpaung. This study used a quantitative experimental method with a one-group pretest–posttest design. The population of the study was all second-grade students of SDN 03 Salimpaung, with a sample of 14 students selected using total sampling. The instrument used to collect data was a test of writing simple sentences. Data analysis techniques included the normality test, homogeneity test, and hypothesis testing using a paired sample t-test. The results showed that the average score of students’ early writing skills increased from 61 in the pretest to 88 in the posttest. The t-test results showed a significance value smaller than α (0.000 < 0.005). This indicates that the Think Talk Write (TTW) learning model has a positive effect on students’ early writing skills. Therefore, the TTW model can be applied in teaching writing in Indonesian language learning.